Generasi Z Dibalik Layar: Dampak Psikologis Penggunaan Media Sosial - fitriana, saskia fitriana saskia (Maliki Interdisciplinary Journal, 2025)
English abstract. Generation Z, who grew up in the digital era, has a high dependence on social media. This study aims to reveal the psychological impacts caused by social media use on this generation. Through a literature review and qualitative data analysis from various sources, this study found that intensive social media use can have a significant impact on the mental health of generation Z. Some of the impacts found include increased anxiety, depression, and sleep disorders. In addition, the emergence of the FOMO (Fear of Missing Out) phenomenon and unhealthy self-comparison with other users are also common problems. This study highlights the importance of awareness of the negative impacts of social media and the need for effective strategies to overcome these problems.